Initial Reports of the Deep Sea Drilling Project 1980
DOI: 10.2973/dsdp.proc.55.131.1980
|View full text |Cite
|
Sign up to set email alerts
|

Rb-Sr Systematics of Basalts from the Hawaiian-Emperor Volcanic Chain

Abstract: RubidiumSr and Rb/Sr for basalts of the Hawaiian-Emperor chain. These data do not support the concept of a mantle isochron indicating a time when the source region for the basalts was established.The source regions for basalts of the Hawaiian-Emperor chain probably lie within the lithospheric plate; the Hawaiian hot spot or melting anomaly is probably an energy source that produced melting in the overlying plate. Variations in Sr isotopic composition within individual volcanoes and between volcanoes indicate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
1
23
1
Order By: Relevance
“…Alkalic lavas from ODP Sites 883 and 1204 on Detroit Seamount, which are considered to represent postshield lavas [ Huang et al , 2005] have lower ɛ Sr than any postshield or posterosional lavas reported from the Hawaiian Islands. Two samples of alkali basalt from Suiko Seamount have ɛ Sr values that are intermediate between those of postshield alkalic lavas from the Hawaiian Islands and from Detroit Seamount [ Lanphere et al , 1980]. ɛ Sr values of most Nintoku lavas are within the range of Hawaiian postshield lavas, but lie at the depleted end of this range (Figures 6 and 16).…”
Section: Discussionmentioning
confidence: 99%
“…Alkalic lavas from ODP Sites 883 and 1204 on Detroit Seamount, which are considered to represent postshield lavas [ Huang et al , 2005] have lower ɛ Sr than any postshield or posterosional lavas reported from the Hawaiian Islands. Two samples of alkali basalt from Suiko Seamount have ɛ Sr values that are intermediate between those of postshield alkalic lavas from the Hawaiian Islands and from Detroit Seamount [ Lanphere et al , 1980]. ɛ Sr values of most Nintoku lavas are within the range of Hawaiian postshield lavas, but lie at the depleted end of this range (Figures 6 and 16).…”
Section: Discussionmentioning
confidence: 99%
“…All samples analyzed for Hf isotope ratios (Tables 1a and 1b) have been previously analyzed for Sr, Nd and Pb isotope ratios. They include 4 samples from Meiji Seamount obtained during DSDP Leg 19 [ Regelous et al , 2003], 28 samples recovered from Detroit Seamount on ODP Legs 145 and 197 [ Regelous et al , 2003; Huang et al , 2005], 4 samples from Suiko Seamount obtained during DSDP Leg 55 [ Lanphere et al , 1980], 16 samples from rejuvenated‐stage lavas, 9 from the Honolulu Volcanics, 7 from the Koloa Volcanics [ Reiners and Nelson , 1998; Lassiter et al , 2000], and 4 samples from the North Arch volcanic field which are geochemically similar to rejuvenated‐stage lavas [ Frey et al , 2000; Yang et al , 2003]. In addition, garnet and clinopyroxene separates from three garnet pyroxenite xenoliths from Salt Lake Crater, Oahu were analyzed for Hf and Nd isotopic ratios.…”
Section: Samplesmentioning
confidence: 99%
“…Our results show that even with consideration of uncertainties arising from age corrections, the sources of Detroit Seamount lavas had lower 87 Sr/ 86 Sr than the sources of Hawaiian lavas. Data sources: Modern Hawaiian shields from GEOROC database; Emperor Seamounts from Lanphere et al [1980], Basu and Faggart [1996], Keller et al [2000], Regelous et al [2003], and Huang et al [2005]. (b) For 176 Hf/ 177 Hf the minimal estimates (data points) of present‐day source ratios are measured 176 Hf/ 177 Hf.…”
Section: Temporal Evolution Of Sr Nd and Hf Isotope Ratios Along Thmentioning
confidence: 99%
“… Dalrymple et al [1980] and Sharp and Clague [2002] reported ages of 64.7 ± 1.1 Ma and 61.3 ± 0.5 Ma, respectively, for Suiko Seamount lavas. Important results are that: (1) like Hawaiian volcanoes, Suiko Seamount has shield stage lavas of tholeiitic basalt overlain by alkalic basalt [ Kirkpatrick et al , 1980]; (2) Initial 87 Sr/ 86 Sr ratios of tholeiitic basalt decrease from Daikakuji Seamount at the Hawaiian‐Emperor bend to Suiko Seamount, which represent over 20 Myr of hot spot activity (∼42–61 Ma, Figure 1a) [ Lanphere et al , 1980].…”
Section: Introductionmentioning
confidence: 99%